Analysis of Indonesian Case-Based Groups with Global Budget Pilot Project Implementation - Alvianto, Muhammad Jihad; Pribadi, Firman (Universitas Muhammadiyah Sidoarjo, 2025)
Background: Indonesia’s pursuit of Universal Health Coverage through Jaminan Kesehatan Nasional (JKN) has faced sustainability challenges, prompting reforms in provider payment systems. Specific Background: The introduction of a mixed-methods model combining Indonesian Case-Based Groups (INA-CBG) and global budget represents a pilot effort to stabilize hospital financing. Knowledge Gap: While national-level reports highlight variability in implementation outcomes, evidence from individual hospitals remains scarce, limiting understanding of operational challenges in different contexts. Aims: This study examined the implementation of the mixed-methods pilot project at ‘Aisyiyah Purworejo General Hospital, focusing on budget allocation, distribution mechanisms, and discrepancies between projections and actual claims. Results: Findings revealed recurrent mismatches between projected budgets and realized claims, driven by declining patient visits, delays in efficiency measures, limited specialist availability, and redistribution of service volume across hospitals. Mid-term utilization reviews reduced the hospital’s budget from IDR 8 billion to IDR 6 billion, with both deficits and surpluses observed across quarters. Novelty: Unlike previous studies, this research highlights the absence of zoning-based patient control and the non-imposition of expenditure risks, offering unique insights into hospital-level dynamics. Implications: These findings inform future health financing policies, particularly regarding risk-sharing models and sustainability of mixed-method payment reforms under JKN. Highlights: Budget projection often mismatched with actual claims due to service shifts. Utilization review reduced hospital budget, revealing financial volatility. No zoning control and no-risk scheme shaped hospital-level outcomes. Keywords: INA-CBG, Global Budget, Health Financing, Hospital Management, Mixed Methods